Low-Profile Dipole Antenna with Corner Cut Parasitic Patches for Bandwidth Enhancement - Kedze, Kam Eucharist; Park, Ikmo (Proceedings of the 2018 IEEE 7th Asia-Pacific Conference on Antennas and Propagation, APCAP 2018, 2018)
A broadband low-profile dipole antenna comprised of a planar radiating half-wavelength dipole element placed above four corner cut parasitic patches on a perfect electric conductor ground plane is presented in this paper. Linearly polarized radiations are generated from the excited dipole and corner cut parasitic patches. Cutting the corners of the parasitic patches significantly enhances the bandwidth of the antenna while maintaining the overall antenna structure at a low profile. These improvements in impedance bandwidth are analyzed and validated by full-wave electromagnetic simulations. The antenna design has overall dimensions of 120 mm x 120 mm x 16.3 mm (0.66λo x 0.66λo x 0.09λo at 1.66 GHz), has aλ10 dB impedance bandwidth of 1.465-1.885 GHz (25.3%), a broadside gain range of 8.47-9.12 dBi, and a radiation efficiency > 98% within the impedance bandwidth.
Keywords: Broadband; Full-wave electromagnetic simulation; Linear polarization; Linearly-polarized radiations; Low-profile antennas; Low-profile dipole antennas; Parasitic patch; Perfect electric conductor; Broadband; corner cut parasitic patch; linear polarization; low-profile antenna